Modeling the diversification of a high-tech enterprise through relocation and supplier recovery - Oleg Fedorovych; Liudmyla Lutai; Andriy Rybka; Yevhenii Polishchuk; Volodymyr Solovyov; Valeriy Fedorovych (Авіаційно-космічна техніка та технологія)
This study addresses the urgent challenge of enterprise diversification to restore high-tech production (aviation technology, UAVs, rocket engineering, etc.) through relocation and modification of component suppliers. The research is particularly relevant for high-tech enterprise recovery during national emergencies and post war reconstruction. Therefore, the topic of the proposed publication, which examines the activities necessary for planning projects related to the diversification of enterprises under threats, is relevant. This study proposes a comprehensive set of mathematical, simulation and agent-based models to facilitate planning for diversification and supply recovery under emergency conditions. This study analyzes existing challenges in enterprise diversification, focusing on relocation due to various threats, including military threats. A systematic analysis of the diversification logistics of high-tech enterprises is conducted. A set of diversification strategies is developed with a special focus on enterprise relocation and supplier recovery. Potential new locations for enterprise relocation are analyzed based on qualitative assessments of key logistical indicators (e.g., safety, infrastructure, and supplier proximity). A set of alternative relocation sites is established, and the most suitable location is selected using lexicographic ordering. The study also focuses on forming a network of component suppliers to consider enterprise relocation and emerging orders, including military applications. The supplier selection and supply routes are optimized using integer (Boolean) programming, accounting for key logistical factors such as component inventory levels, delivery time, costs, and supply risks. To analyze the dynamic process of transporting technological equipment and components, a simulation model was developed using the AnyLogic agent-based platform. A set of agents is formed that represents the main logistical events for planning the enterprise relocation. Based on the simulation results, key relocation indicators are assessed, including location selection, supplier network formation, supply route optimization, delivery time, and inventory levels. The scientific novelty of this research lies in the development of original models that determine a new location for high-tech enterprises, form a network of suppliers to meet production needs, establish supply routes and evaluate feasibility and risks in executing a diversification plan under special conditions. These findings are highly relevant for planning diversification processes in high-tech production, justifying enterprise relocation decisions, approving supplier networks and forming rational and secure supply routes under threat conditions. These efforts ensure the effective recovery of high-tech production during national emergencies and post war reconstruction.